2011
DOI: 10.1097/mco.0b013e328346df65
|View full text |Cite
|
Sign up to set email alerts
|

Innate and learned preferences for sweet taste during childhood

Abstract: An examination of the basic biology of sweet taste during childhood provides insight, as well as new perspectives, for how to modify children's preferences for and intakes of sweet foods to improve their diet quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
154
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(176 citation statements)
references
References 55 publications
5
154
0
11
Order By: Relevance
“…Similarly, research has shown that introduction to sugary foods early in life can influence preferences and consumption of sweet foods later in life (Avena et al . 2008; Ventura & Mennella 2011). Half of children 6–23 months of age in this study had consumed a sweet commercially produced snack food product or sweetened beverage on the preceding day.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research has shown that introduction to sugary foods early in life can influence preferences and consumption of sweet foods later in life (Avena et al . 2008; Ventura & Mennella 2011). Half of children 6–23 months of age in this study had consumed a sweet commercially produced snack food product or sweetened beverage on the preceding day.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Preschool children typically consume a narrow variety of foods, which includes low quantities of vegetables. 7 This is thought to be secondary to young children's innate preference for sweet foods, 8 avoidance of new foods, 9 and limited exposure to fruits and vegetables by caregivers. 10 To address the obesity epidemic for this young age group it is recommended that caregivers provide children with repeated exposures to fruits and vegetables and enthusiastically model consumption, as young children are influenced by adult dietary behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Infants and other mammals show an inherent 46 liking for sweetness that is present from birth (Steiner 1979, Ventura andMennella 2011). 47 'Sweet-calorie learning' in humans 7 satiation, and 4) expected sickliness (see below for details).…”
Section: Introduction 44mentioning
confidence: 99%